2017
DOI: 10.3857/roj.2017.00108
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary team approach for the management of patients with locally advanced non-small cell lung cancer: searching the evidence to guide the decision

Abstract: Locally advanced non-small cell lung cancer (LA-NSCLC) is composed of heterogeneous subgroups that require a multidisciplinary team approach in order to ensure optimal therapy for each patient. Since 2010, the National Comprehensive Cancer Network has recommended chemoradiation therapy (CRT) for bulky mediastinal disease and surgical combination for those patients with single-station N2 involvement who respond to neoadjuvant therapy. According to lung cancer tumor boards, thoracic surgeons make a decision on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Generally, patients who initiated cCRT were younger, had a better predicted PS score, and a lower CCI compared to patients who received single modality therapy. This is in line with prior research conducted by Oh et al (2017), which shows that cCRT is generally administered to healthier patients who are younger in age, and have minimal to no comorbidities, as well as the 2003 ASCO clinical practice guideline [17,28]. In this analysis, patients receiving cCRT had significantly better survival compared to patients receiving single modality therapy, which may be in part due to younger age and better predicted PS.…”
Section: Plos Onesupporting
confidence: 87%
See 1 more Smart Citation
“…Generally, patients who initiated cCRT were younger, had a better predicted PS score, and a lower CCI compared to patients who received single modality therapy. This is in line with prior research conducted by Oh et al (2017), which shows that cCRT is generally administered to healthier patients who are younger in age, and have minimal to no comorbidities, as well as the 2003 ASCO clinical practice guideline [17,28]. In this analysis, patients receiving cCRT had significantly better survival compared to patients receiving single modality therapy, which may be in part due to younger age and better predicted PS.…”
Section: Plos Onesupporting
confidence: 87%
“…The administration of specialized multimodality therapy requires integrative knowledge on prognostic and predictive factors associated with survival in this patient population [17]. Ideally, these complex treatment decisions should be made by a multidisciplinary team (MDT) of physicians and care-givers in close coordination, as it has been shown that health outcomes improve for NSCLC patients when treatment is directed by an MDT [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…For inoperable patients, in several studies, platinum‐based concurrent chemoradiotherapy was performed for patients with LA‐NSCLC, and the 2‐year high overall survival (OS) rate was approximately 50%‐60% . However, in contrast to its survival benefit, concurrent chemoradiotherapy induces severe hematologic toxicity, infection, esophagitis and pneumonitis; therefore, chemoradiotherapy is sometimes a heavy burden in elderly patients or patients with severe comorbidities . As an alternative treatment option, radiotherapy alone or low‐dose carboplatin‐based concurrent chemotherapy is sometimes introduced to patients, but such patients have a 2‐year OS rate of approximately 5%‐40%, with a poor prognosis …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] However, in contrast to its survival benefit, concurrent chemoradiotherapy induces severe hematologic toxicity, infection, esophagitis and pneumonitis; therefore, chemoradiotherapy is sometimes a heavy burden in elderly patients or patients with severe comorbidities. [6][7][8] As an alternative treatment option, radiotherapy alone or low-dose carboplatin-based concurrent chemotherapy is sometimes introduced to patients, but such patients have a 2-year OS rate of approximately 5%-40%, with a poor prognosis. 9,10 Carbon-ion radiotherapy (CIRT) is a high linear energy transfer radiotherapy that is being widely used across Europe and Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Other potentially fatal conditions, such a malignancies, are usually discussed by multidisciplinary specialist boards to provide optimal therapy for each individual from the start, including access to the most novel agents in the context of ongoing research projects aiming to continuously expand and improve the standard of treatment. Therapy for drug‐resistant TB is often initiated by nursing staff based on algorithms and limited information about the host and the pathogen .…”
Section: Novel Drug Treatments For Mdr‐tbmentioning
confidence: 99%